INFLUENCE OF MEDIA ON SEXUAL HEALTH PERCEPTIONS OF SELECTED 4TH YEAR COLLEGE STUDENTS AT BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study investigates the influence of social media on the sexual health perceptions of fourth-year college students. As digital platforms become increasingly prominent sources of information, it is important to assess how exposure to online content shapes students’ knowledge, attitudes, and decision-making regarding sexual health. The research examines key factors such as demographic profiles, patterns of social media usage, and the nature of sexual health content encountered online. Through this analysis, the study aims to determine the extent to which social media contributes to shaping young adults’ understanding and perspectives on sexual health. This study utilized a quantitative correlational research design to examine the relationship between social media exposure and sexual health perceptions among college students. A stratified random sampling technique was employed to select 342 fourth-year students from three academic programs at Bestlink College of the Philippines. Data were collected through a standardized, in-person survey questionnaire that measured levels of media exposure and perceptions related to sexual health. Statistical analysis was conducted to determine the presence and strength of any significant correlations between media consumption and students’ sexual health perceptions. The results reveal no statistically significant relationship between media exposure and students’ perceptions of sexual health. Nevertheless, the study emphasizes that the media continues to serve as a key source of sexual health information, offering accessible educational resources and enhancing general awareness. While media exposure may not directly influence perceptions, it plays an important role in disseminating knowledge and supporting students in making informed decisions about their sexual health. In light of the findings, the study recommends enhancing sexual health education by incorporating accurate, evidence-based media content—such as news articles, educational videos, and interactive learning tools—to provide students with comprehensive and accessible information. It also suggests that universities implement targeted awareness campaigns to address misconceptions and fill gaps in students’ understanding of sexual health. Additionally, the integration of comprehensive sex education into the academic curriculum is strongly encouraged to ensure students are equipped with reliable, science-based knowledge that supports informed decision-making and responsible behavior.  .
Keywords: sexual health education; media content; evidence-based information; university programs; awareness campaigns; comprehensive sex education; informed decision-making; responsible behavior; student health; curriculum integration